Experimental study of preparing sulfuric acid from sulfur dioxide using catalytic photosynthesis method - Telun, Floris (2010)

(untitled)
Sulfuric acid is an acid that is commonly used worldwide in various fields especially in chemical field. In fact, the demand for sulfuric acid increases nowadays due to its benefits. In the process of producing sulfuric acid (H2SO4), the most common processes that have been used worldwide are lead chamber process, contact process and wet sulfuric acid gas process. Sulfur dioxide usually known as a dangerous gas as it causes acid rain once it has been emitted to the air. But on the other hand, it can be a beneficial gas because sulfur dioxide (SO2) normally used as a feed to produce sulfuric acid. Thus, catalytic photosynthesis method will be used in this research study where chemical reaction is induced by light. This study will be conducted using a simple method which using a stainless steel reactor with a high intensity photosynthesis lamp. The sulfur dioxide (SO2) will be fed under different flow rate (20, 60 and 100 ml/h) and the reaction will be contacted for about 1 to 2 hours. In the end of the study, different flow rate of the sulfur dioxide (SO2) will affect the pH reading of the product. The pH of the product which is sulfuric acid (H2SO4) will be analyzed using pH meter as well the composition will be analyzed by FTIR (Fourier Transform Infrared Spectroscopy).